Banksia born to burn - He, Tianhua; Lamont, Byron; Downes, K. (Blackwell Science Limited, 2011)
Historical evidence of recurrent fire in many of the world's biomes suggests that fire may have had profound evolutionary influences on their extant floras. However, the role of fire as a selective force in the origin and evolution of plant traits remains controversial. Using Bayesian Monte-Carlo-Markov-Chain procedures and calibration points from the fossil record, we generated a dated phylogeny for the iconic Australian genus Banksia, and reconstructed the evolutionary/chronological position of five putatively fire-related traits. The fire-dependent trait, on-plant seed storage (serotiny), and associated fire-enhancing trait, dead floret retention, co-originated with the first appearance of Banksia 60.8 million yr ago (Palaeocene). Whether nonsprouting or resprouting is ancestral was indeterminable, but the first banksias were nonclonal. Derived traits, such as dead leaf retention (fire-enhancing) and clonality (underground budbanks; fire-avoiding), first appeared 26-16 million yr ago (Miocene) with the onset of seasonal drought and thus more frequent fire, and culminated in dead florets/bracts completely covering the persistent fruits in some species. Thus, fire may have been a selective force in the very origin of Banksia 40 million yr before the onset of climate seasonality in the Miocene, and continued to have an impact on the direction of evolution, favouring traits consistent with adaptation to an increasingly (sometimes less) fire-prone environment.